1998
DOI: 10.1046/j.1365-2842.1998.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Leached components from dental composites in oral simulating fluids and the resultant composite strengths

Abstract: The aim of this study was to analyse the leached moieties of dental composites after storage in ethanol and organic acids of plaque and further evaluate the resultant effect on the diametral tensile strength (DTS) of the composites. Three commercial composites were used: Bis-GMA-based Z100, Bis-GMA/UDMA-based Heliomolar, and Bis-MPEPP-based Marathon One. The solutions used were: 99.9% acetic acid, 99% propionic acid and 75% ethanol. Specimens (4 mm diam. x 2 mm thick) were stored at 37 degrees C in 3 mL of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
121
1
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 17 publications
8
121
1
8
Order By: Relevance
“…Therefore, in the case of RBCs, degradation typically occurs because of these two reasons: (1) hydrolytic breakdown of the bond between the silane and filler particles and the fillerresin matrix, resulting in debonding ultimately; and (2) the softening of dental resins through the plasticizing action of water 9) . As for the effects of solvents on dental composites, many factors come into play -such as the hydrophilicity of polymers andthecrosslinkingdensityofthenetwork 10) . Recently, Weinmann et al 11) reported on the synthesis of a new monomer system named "silorane", which is obtained from the reaction of oxirane and siloxane molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the case of RBCs, degradation typically occurs because of these two reasons: (1) hydrolytic breakdown of the bond between the silane and filler particles and the fillerresin matrix, resulting in debonding ultimately; and (2) the softening of dental resins through the plasticizing action of water 9) . As for the effects of solvents on dental composites, many factors come into play -such as the hydrophilicity of polymers andthecrosslinkingdensityofthenetwork 10) . Recently, Weinmann et al 11) reported on the synthesis of a new monomer system named "silorane", which is obtained from the reaction of oxirane and siloxane molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors contribute to the elution of components from resin-based materials -namely amount of unreacted monomers, size and chemical composition of elutable species, and chemistry of the solvent 16,27) . Many mouthrinses include ethanol in their composition, and ethanol may accelerate the hydrolytic degradation of resin-based materials 28) . On this ground, subsurface and surface degradation of resin composites can be reproduced in the laboratory by storage in 50:50 ethanol:water solution 29,30) , which is listed as a food-simulating liquid in the U.S. Food and Drug Administration (FDA) Guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation process can also be influenced by powers on the radical formation of bleaching materials and their PH alongside their contact time. (17,20,22,23) The effect of each prescribed reason can affect the results of different studies, and different results for surface roughness are not affected only by one main factor.…”
Section: Discussionmentioning
confidence: 99%